VD_FINDINFO AA 62/11 - 106/2012 vom 5. November 2012 - VD Tribunal cantonal (2012)
ADOPTION, RENTE D'ORPHELIN, DROIT INTERNATIONAL PRIVÉ, FILIATION, ACCORD SUR LA LIBRE CIRCULATION DES PERSONNES, DROIT ÉTRANGER | 1 Annexe II ALCP, 267 CC, 30 LAA, 78 LDIP, 21 LLCA, 40 OLAA, 1 Règl. 1408/71, 78 Règl. 1408/71